The importance of cardiac tomography in the evaluation of cardiac changes and coronary atherosclerosis in patients with betathalassemia major - Stancă, Ionuț; Rizea, Ileana Olguta; Popescu, Andreea Caterina; Albu, Alice; Rus, Mihaela; Fica, Simona (Technium Social Sciences Journal, 2020)
Betathalassemic patients demonstrate an increased rate of extracardiac vascular complications, but very low prevalence for coronary artery disease. Computed tomography (CT) achieves excellent tissue characterization, with high spatial resolution and has developed as a gold standard for noninvasive angiography and calcium score assessment. Methods. We examined 7 patients with major beta-thalassemia and 7 patients who had an indication for cardiac CT for resting ECG changes, without symptoms of angina pectoris. We investigated the coronary atherosclerosis by assessing the coronary artery calcium (CAC) and arterial stifness. Usual tests and echocardiography measurement were performed. Cardiac computed tomography determined left ventricular mass, left ventricular ejection fraction (LVEF), coronary calcium score and coronary anatomy. An analysis of myocardial density was also performed. Artery stiffness was assessed by the cardio ankle vascular index (CAVI). Results. Arterial stiffness index in betathallasemic group was higher than control group, R-CAVI index was 6.21± 0.49 vs 5.65±0.37 and L-CAVI index was 6.21± 0.38 vs 5.71±0.31. The assessment of systolic function by echocardiography and cardiac CT examination in the 2 groups, shows that the LVEF in the betathallasemic group was significantly lower than in the control group, which means that some patients already had cardiomyopathy. LV myocardial mass was significantly higher in the group with beta-thalassemia, which is explained by the appearance of myocardial remodeling. The calcium score in patients with major beta-thalassemia was 0 and 8,5± 5,9 in the control group. Only 3 patients (42,8%) in the control group had a calcium score > 10U. No atherosclerotic lesions were observed in patients with major beta-thalassemia, whereas the control group showed mild coronary atherosclerotic lesions. If myocardial density can be determined, calcium or iron deposits can be detected in the myocardium. In patients with beta-thalassemia, the density of the myocardium was higher, both in the left ventricle (49.29 8.87±HU) and in the septum (56.71± 8.1 HU). Calculation of Pearson’s correlation coefficient revealed a good association between CT and echocardiography, reproducibility of CT was significantly higher on an intra-observer level for LVEF and LV Mass. Conclusions: Patients with ?–thalassemia major have a similar calcium score compared to control subjects, but they have an increase in arterial stiffness. However, zero frequencie of coronary heart disease, denotes coronary protection mechanisms in thalassemia, so future research should focus on the anti-atherogenic potential of blood lipids at these patients. The ability of cardiac tomography to detect calcifications and changes in myocardial density should be valued, as it can be a good tool for establishing the diagnosis of cardiomyopathy by iron loading.